The Wiley encyclopedia of packaging technology - Yam, Kit L. (Hoboken, NJ : John Wiley & Sons, 2009)
* Provides information on every stage of the packaging process and extensive bibliography, written by renowned experts from around the world * Based on the content and format of previous editions with additions, revisions, and modernization of the content reflecting changes and developments in the field over the past decade.
Includes bibliographical references and index
Keywords: Packaging -- Dictionaries